2019
DOI: 10.1002/art.40727
|View full text |Cite
|
Sign up to set email alerts
|

Serum S100A8/A9 and S100A12 Levels in Children With Polyarticular Forms of Juvenile Idiopathic Arthritis: Relationship to Maintenance of Clinically Inactive Disease During Anti–Tumor Necrosis Factor Therapy and Occurrence of Disease Flare After Discontinuation of Therapy

Abstract: Serum S100 levels did not predict maintenance of CID or disease flare, with S100A12 levels only moderately correlating inversely with time to disease flare. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 39 publications
2
42
2
Order By: Relevance
“…Our study did not show an association between S100 proteins and articular disease activity in patients with JIA. This finding aligns with lack of S100 proteins ability in predicting flares in nonsystemic polyarticular JIA patients per a recent report from our group [13]. However, in the sJIA subset, the levels of S100 proteins were associated with disease activity for systemic symptoms (fever and rash), indicating the potential utility of S100 proteins in monitoring disease course in this subset of patients.…”
Section: Discussionsupporting
confidence: 90%
“…Our study did not show an association between S100 proteins and articular disease activity in patients with JIA. This finding aligns with lack of S100 proteins ability in predicting flares in nonsystemic polyarticular JIA patients per a recent report from our group [13]. However, in the sJIA subset, the levels of S100 proteins were associated with disease activity for systemic symptoms (fever and rash), indicating the potential utility of S100 proteins in monitoring disease course in this subset of patients.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, increased MRP8/14 levels in patients with inactive disease predicted subsequent flares [ 6 , 8 , 9 ]. Notwithstanding these promising results, a recent article on 137 JIA patients with clinically inactive disease could not confirm that MRP8/14 levels before anti-TNF withdrawal had any value for the prediction of flares [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is conflicting evidence on the ability of S100 proteins to predict disease flare. A multicentre prospective study of 130 children with extended oligoarticular and polyarticular JIA revealed no correlation between serum levels of S100A8/9 prior to discontinuation of anti-TNF therapy and future flare, and weak correlation between serum S100A12 and future flare 87 . These conflicting conclusions between studies might be due to discontinuation of different drugs, use of different assays or selection of different outcome measures.…”
Section: Biological Markers Predicting Flare In Jiamentioning
confidence: 99%